A Theoretical and Clinical Framework for Parental Burnout: The Balance Between Risks and Resources (BR2) - Mikolajczak, Moïra; Roskam, Isabelle (Frontiers in Psychology, 2018)
Parental burnout is a specific syndrome resulting from enduring exposure to chronic parenting stress. But why do some parents burn out while others, facing the same stressors, do not? The main aim of this paper was to propose a theory of parental burnout capable of predicting (for prevention purposes) who is at risk of burnout, explaining (for intervention purposes) why a particular parent burned out and why at that specific point in time, and providing directions for intervention. The secondary goal was to operationalize this theory in a tool that would be easy to use for both researchers and clinicians. The results of this two-wave longitudinal study conducted on 923 parents suggest that the Balance between Risks and Resources (BR2) theory proposed here is a relevant framework to predict and explain parental burnout. More specifically, the results show that (1) the BR2 instrument reliably measures parents' balance between risks (parental stress-enhancing factors) and resources (parental stress-alleviating factors), (2) there is a strong linear relationship between BR2 score and parental burnout, (3) parental burnout results from a chronic imbalance of risks over resources, (4) BR2 predicts parental burnout better than job burnout and (5) among the risk and resource factors measured in BR2, risks and resources non-specific to parenting (e.g., low stress-management abilities, perfectionism) equally predict parental and job burnout, while risks and resources specific to parenting (e.g., childrearing practices, coparenting) uniquely predict parental burnout.